2023
DOI: 10.1186/s40359-023-01131-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiential COVID-19 factors predicting resilience among Spanish adults

Abstract: Background The pandemic caused by COVID-19 has meant for spanish citizens a constant adaptation to health measures in order to try to stop transmission of the virus. During this adaptation process, different psychosocial aspects have caused consequences for people?s mental health to a greater or lesser extent. Makes sense of an emotional torrent who has gone through fear, anxiety, loneliness and anger. The interaction between perception and reality has given rise to situations where loneliness … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Resilience has been highlighted as a crucial protective factor during times of crisis [ 53 ]. There are a few research studies that looked into how resilience changed throughout the COVID-19 epidemic, and, consistent with our current findings, they found that resilience scores did not change significantly over time during the pandemic [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resilience has been highlighted as a crucial protective factor during times of crisis [ 53 ]. There are a few research studies that looked into how resilience changed throughout the COVID-19 epidemic, and, consistent with our current findings, they found that resilience scores did not change significantly over time during the pandemic [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire reflects the area of teachers' subjective emotional experience of the feelings they perceive when using online tools in teaching. In relation to this variable, it was desirable to include the reasons for the perceived burden of Secondary School Teachers' Attitudes Towards Online Learning Tools: Teachers' Behaviour in Distance Education teachers in distance education during the pandemic [5], [6], [7], [26]. These variables enrich the research in another interesting pedagogical and psychological area.…”
Section: Mentimetermentioning
confidence: 99%
“…There was a lack of social interaction and interpersonal support among colleagues [4]. Long-term stressors in the form of psychological, social, and physical strain can escalate into ineffective rigid teaching, negative workplace relationships, low self-esteem, health problems, leaving the teaching profession, or burnout syndrome [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%